1977
DOI: 10.1210/endo-100-5-1284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Somatostatin on Neurotensin-Induced Glucagon Release and Hyperglycemia

Abstract: Administration of neurotensin to dogs resulted in rises in circulating blood glucose, glucagon and insulin levels, the rise in glucagon being more pronounced than that in insulin. Infusion of somatostatin along with neurotensin suppressed glucagon and insulin responses to neurotensin and prevented the rise in blood glucose levels. These results suggest that the hyperglycemia seen after neurotensin is due to neurotensin stimulation of glucagon release over insulin release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
8
0

Year Published

1979
1979
2003
2003

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 0 publications
3
8
0
Order By: Relevance
“…Neurotensin has been shown to induce hyperglycemia (3)(4)(5)(6)(7)(8) and this has been attributed to a stimulation of glucagon release associated with an inhibition of insulin release (3). It has recently been reported that neurotensin directly inhibits insulin release and stimulates glucagon release by isolated pancreatic islets (9).…”
mentioning
confidence: 99%
“…Neurotensin has been shown to induce hyperglycemia (3)(4)(5)(6)(7)(8) and this has been attributed to a stimulation of glucagon release associated with an inhibition of insulin release (3). It has recently been reported that neurotensin directly inhibits insulin release and stimulates glucagon release by isolated pancreatic islets (9).…”
mentioning
confidence: 99%
“…Neurotensin has been reported to stimulate release of thyrotropin in rats [49] and insulin and glucagon in dogs [50]. Other similar studies showed that neurotensin prevents atrophy of the intestinal mucosa associated with TPN and promotes the release of secretory IgA and IgM into the bile [51].…”
Section: Neurotensinmentioning
confidence: 99%
“…On the other hand, Patton et al (1976) suggested that the hyperglycemic effect might be mediated by such a decrease in insulin, and/or an increase in glucagon. Hyperglucagonemia and hypoinsulinemia were observed in anesthetized rats , and moderate hyperinsulinemia and exaggerated hyperglucagonemia were also seen in dogs (Ukai et al 1977).…”
mentioning
confidence: 93%
“…In addition, neurotensin has been found to induce hyperglycemia in the rat and dog ; Nagai and Frohman 1976;Rosell et al 1976; Ukai et al 1977). This hyperglycemic effect seemed to be due to stimulation of hepatic glycogenolysis by its direct or indirect action.…”
mentioning
confidence: 99%